Kecanduan Game Online sebagai Gejala Nekrofilia Sosial: Analisis Humanistik Erich Fromm dalam Masyarakat Digital - Sudarso, Yosep; Boymau, Yerliani; Seo, Marwela R.; Djawa, Maya (Balai Diklat Keagamaan Denpasar, 2025)
This article explores the phenomenon of online game addiction in digital society through the lens of Erich Fromm’s theory of necrophilia. Fromm interprets necrophilia not merely as a sexual disorder but as a personality orientation that favors the dead, static, and mechanical. Employing a descriptive qualitative approach with a humanistic analysis, this study investigates how game addiction reflects social necrophilic symptoms and affects interpersonal relationships and psychosocial life. Findings indicate that game addiction is not only a behavioral issue but a sign of modern human alienation from authentic and living relationships. Fromm proposes biophilia—a love of life—as a counterpoint, highlighting the importance of human connection, empathy, and life values. The study recommends value-based education and the development of a healthy digital culture as both preventive and curative strategies against game addiction. Keywords:Social nekriphilia, Game Addiction, Erivh Fromm, Digital Society